Adolescent and emerging adults' evaluation of a Facebook site providing sexual health education. Issue 1 (1st October 2018) - Jones, Krista; Williams, Jeff; Sipsma, Heather; Patil, Crystal
Abstract: Objective: To explore participants' evaluation of an online sexual health intervention posted on Facebook and identify appealing and effective ways to present sexual health content to adolescents and emerging adults (AEAs). Design and Measures: A qualitative approach using peer moderated focus groups was used to elicit reflections on the Facebook site's content, appeal, and ease of navigation. Focus group discussions were transcribed, coded, and analyzed for themes using conventional content analysis. Demographic data were analyzed with SPSS. Sample: Participants ( n  = 63) were recruited from a Midwestern university and both an urban and rural high school. Eight focus groups were conducted. Results: Participants reported significant concerns with the stigma associated with having sexual health conversations with parents, peers or providers. Participants thought the Facebook site provided reliable sexual health information, was not condescending, and was more visually appealing than other sites frequented by technology‐proficient AEA. AEAs suggested developing an independent sexual health education website. Conclusion: Findings demonstrate the importance for having accurate and reliable sexual health information available on the internet. The use of visually appealing social media to communicate sexual health content that is interactive, informative, and user‐friendly and meets the educational needs of AEA in the Midwest is recommended.